METODE PENGENDALIAN PERSEDIAAN BAHAN BAKU CRUDE COCONUT OIL YANG OPTIMAL PADA PT. PSE - Fadlillah, Siti Nur; Andreas, Andreas; Zahedi, Zahedi (Industrial and Systems Engineering Assessment Journal (INASEA), 2008)
The inventory system is one of the most important managerial functions, since vast majority of companies has large investment involved in this aspect. This also applies to PT. Palko Sari Eka that is big in the field of inventory planning and production control. PT. Palko Sari Eka, as one company in the oil refinery industry, strives to optimize the inventory of raw materials Crude Coconut Oil by trying to compare different methods of inventory control methods such as the EOQ (Economic Order Quantity, method of EOI (Economic Order Interval), Min-Max method. Crude Coconut Oil is one of the major raw material products, which require a good inventory system. From the results of research conducted, it turns out the character of stochastic demand data, it is also necessary to conduct simulations to obtain results closer to the actual conditions. The inventory criteria can be said to be optimal if the total annual cost is minimum. It is concluded that the best method is the Fixed Size Order Systems (EOQ) with an order of 2770 mT per order.